Maestros and mythologies: some lockdown reflections. Issue 1 (17th July 2020) - Lizieri, Colin
Abstract : Purpose: The paper reflects upon the tendency of participants in the commercial real estate markets to give excess status to individuals in decision-making and to hold beliefs that are at best weakly supported empirically. Design/methodology/approach: The paper is reflexive in nature, using experiential reflection to consider institutional processes in the real estate market. It is important to use "methodology" correctly and not as a synonym of "method". Findings: Using reflexive mode, the paper does not have "findings" as such: if the views expressed are accepted, then a research agenda to understand decision-making processes is implied. Research limitations/implications: The nature of reflection is that it follows from the writer's experiential processes and interpretations. The reader may come from a different stance. Broadly accepting the propositions points to the need for a contextual analysis of decision-making processes in private real estate and consideration of the implications of privileging individual idiosyncratic decisions over analytic procedures. Practical implications: Prior research has demonstrated the lack of a back-testing culture in real estate that would allow empirical analysis of the consequences of "gut feel" decisions overriding modelled analysis; further, entrenched beliefs about the drivers of market performance might result in misallocation of resources. Social implications: Resource allocation in commercial real estate has important consequences for land use and urban and regional development. Originality/value: The paper reflects the views and experience of the author based on over 30 years of research into commercial real estate.